Conformational Analysis and Binding Properties of a Cavity Containing Porphyrin Catalyst Provided with Urea Functions. Issue 26 (19th August 2016) - Hidalgo Ramos, Pilar; Saisaha, Pattama; Elemans, Johannes A. A. W.; Rowan, Alan E.; Nolte, Roeland J. M.
Abstract : Urea‐functionalized porphyrin catalysts containing a cavity, which are used for the processive epoxidation of polymers, are thoroughly characterized and their binding properties and other supramolecular features disclosed. Intramolecular coordination of the urea side chains to the metal center of the porphyrin moiety is unveiled through NMR, IR, UV, and fluorescence spectroscopy studies. This intramolecular coordination appears to be essential in order to facilitate catalysis in a pseudo‐rotaxane fashion, i.e. by preventing the use of an excess of bulky axial ligands. The current investigation provides information on how to modulate in a dynamic fashion the catalytic activity of supramolecular systems, which is of interest for the design of increasingly efficient processive catalysts. Abstract : Diphenylglycoluril‐based metalloporphyrin cavities functionalized with alkylurea chains show intramolecular coordination of one of these chains to the metalloporphyrin. Its impact on the binding of viologen guests inside the cavity and coordination of axial ligands at the outside is described, and allosteric binding effects are revealed.